High efficiency slotted photonic crystal waveguides for the determination of gases using mid-infrared spectroscopy. Issue 5 (3rd September 2018) - Kassa-Baghdouche, Lazhar; Cassan, Eric
ABSTRACT: We present the design and analysis of a high efficiency slotted photonic crystal waveguide for gas sensing applications in the mid-infrared wavelength range. We designed the slotted photonic crystal waveguide structure by engineering the interfaces between the input and output slot waveguides and a resonant coupler. Coupling and transmission spectra of the sensor have been modeled using the three-dimensional finite-difference time domain method. The sensing principle is based on the shift of the upper band edge of the sensor output transmission spectrum which arises due to changes in the ambient refractive index. Transmission spectrum and sensitivity of the proposed sensor are analyzed by tuning the radii of the air holes localized on each side of the slot. The results show that a change of the refractive index of the gas by 10 −4 leads to a shift of the upper band edge wavelength by 540 pm which corresponding to a sensitivity of 1720 nm per refractive index unit. The proposed design may be an ideal platform for developing mid-infrared gas sensing devices characterized by high coupling efficiencies and high sensitivities.